A novel motion sensor-driven control system for FES-assisted walking after spinal cord injury: A pilot study - Braz, Gustavo P.; Russold, Michael F.; Fornusek, Che; Hamzaid, Nur Azah; Smith, Richard M.; Davis, Glen M. (Elsevier, 2016)
This pilot study reports the development of a novel closed-loop (CL) FES-gait control system, which employed a finite-state controller that processed kinematic feedback from four miniaturized motion sensors. This strategy automated the control of knee extension via quadriceps and gluteus stimulation during the stance phase of gait on the supporting leg, and managed the stimulation delivered to the common peroneal nerve (CPN) during swing-phase on the contra-lateral limb. The control system was assessed against a traditional open-loop (OL) system on two sensorimotor ‘complete’ paraplegic subjects. A biomechanical analysis revealed that the closed-loop control of leg swing was efficient, but without major advantages compared to OL. CL automated the control of knee extension during the stance phase of gait and for this reason was the method of preference by the subjects. For the first time, a feedback control system with a simplified configuration of four miniaturized sensors allowed the addition of instruments to collect the data of multiple physiological and biomechanical variables during FES-evoked gait. In this pilot study of two sensorimotor complete paraplegic individuals, CL ameliorated certain drawbacks of current OL systems – it required less user intervention and accounted for the inter-subject differences in their stimulation requirements.